Caracterização química, atividade antioxidante e avaliação da bioacessibilidade de componentes bioativos de Sterculia striata A.St.Hil. & Naudin (chichá) em comparação com a Arachis hypogaea L. (amendoim) - Sarah Morais Senna Prates (2018)
Brazil is one of the most megadiverse countries in the world and is home to about 20% of all the world's biological diversity. Cerrado represents the second largest biome in the Brazilian territory, with an area of approximately 2 million km2. Despite presenting great biological diversity and high levels of endemism, cerrado is suffering a critical risks of degradation. The negative perspective on preserving Brazilian native species highlights the need to recover information about the use of these plants. In this context, the Sterculia striata A. St.-Hil. & Naudin, native species of the cerrado known as chichá and amendoim de macaco, has been selected for this study. The main goal was to value the bioactive potential of the S. striata almonds, aiming its exploitation as a functional food. The specific objectives were to trace the phytochemical and fatty acid profiles, to quantify the phenolic compounds, to evaluate the antioxidant capacity and to determine the bioaccessibility of bioactive components of the chichá. The results were compared with those obtained for Arachis hypogaea (peanut). The analyzes were performed with fresh and toasted samples, of both plants. The profiles of flavonoids and phenolic acids were determined by CLAE/DAD. The total of phenolic compounds was qualified by spectrophotometry by the Folin-Ciocalteau method, and the antioxidant activity was evaluated by ABTS, DPPH and FRAP methods. After the in vitro digestion test, the changes in the flavonoid and phenolic acid profile were evaluated, as well as the bioaccessibility of total polyphenols and lipids. CLAE identified the presence of rutin in S. striata and A. hypogaea, and phenolic acids a other flavonoids as well. In the characterization by GC, both oils presented predominance of MUFAs, with higher contribution of oleic acid. The almonds of S. striata presented lower antioxidant activity than the peanuts and it may be a consequence of lower concentration of polyphenols, observed in the trials. After in vitro digestion, the profile of phenolic acids and flavonoids was altered. In S. striata digestion degraded some compounds, but other substances became more evident. Already in A. hypogaea digestion degraded, but also formed new compounds. After in vitro digestion, the concentration of rutin was increased in all samples, except for A. hypogaea roasted. In this sample, the rutin was transformed into quercetin. The bioaccessibility of the phenolic compounds increased, after the digestion, in all in natura samples. The lipid bioaccessibility was lower in S. striata then in A. hypogaea. The toasted samples had higher percentages of bioaccessible lipids than the samples in natura. These results indicate that S. striata almond can be considered a food with functional potential. Further studies should be done for this to be confirmed